ANALISIS KORELASI KANONIKAL KOMPONEN AKTIVA DAN PASIVA - Baldric Siregar (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
The independence of asset and liability composition is obvious in Modigliani andMiller’s capital structure proposition. While, independence of investing and financingdecisions is a very useful assumption to simplify corporate financial decisions, the actualbalance sheets of corporations do not reveal independence between the two sides of thebalance sheet. The purposes of this paper are to empirically identify relationship betweenthe structures of left side and right side of balance sheet and to explain the nature of theserelationships by using canonical correlation analysis. Canonical correlation analysis showsthat firms match the maturity structure of their assets and liabilities, short-term (long-term)assets tend to be financed with short-term (long-term) liabilities, accounts receivable areused as collateral for short-term loan, and fixed assets are use as collateral for long-termloan.